Irreversible Electroporation: An Emerging Immunomodulatory Therapy on Solid Tumors - Zhang, Nana; Li, Zhuoqun; Han, Xuan; Zhu, Ziyu; Li, Zhujun; Zhao, Yan; Liu, Zhijun; Lv, Yi (Frontiers in Immunology, 2022)
Irreversible electroporation (IRE), a novel non-thermal ablation technique, is utilized to ablate unresectable solid tumors and demonstrates favorable safety and efficacy in the clinic. IRE applies electric pulses to alter the cell transmembrane voltage and causes nanometer-sized membrane defects or pores in the cells, which leads to loss of cell homeostasis and ultimately results in cell death. The major drawbacks of IRE are incomplete ablation and susceptibility to recurrence, which limit its clinical application. Recent studies have shown that IRE promotes the massive release of intracellular concealed tumor antigens that become an “in-situ tumor vaccine,” inducing a potential antitumor immune response to kill residual tumor cells after ablation and inhibiting local recurrence and distant metastasis. Therefore, IRE can be regarded as a potential immunomodulatory therapy, and combined with immunotherapy, it can exhibit synergistic treatment effects on malignant tumors, which provides broad application prospects for tumor treatment. This work reviewed the current status of the clinical efficacy of IRE in tumor treatment, summarized the characteristics of local and systemic immune responses induced by IRE in tumor-bearing organisms, and analyzed the specific mechanisms of the IRE-induced immune response. Moreover, we reviewed the current research progress of IRE combined with immunotherapy in the treatment of solid tumors. Based on the findings, we present deficiencies of current preclinical studies of animal models and analyze possible reasons and solutions. We also propose possible demands for clinical research. This review aimed to provide theoretical and practical guidance for the combination of IRE with immunotherapy in the treatment of malignant tumors.